An examination of participation of rural women in local governance: the case of Mutasa rural district - Chikovha, Abigail (Midlands State University, 2017)
This study examines the level and forms of participation of rural women in local governance in Zimbabwe with a focus on Mutasa Rural District in Manicaland Province. The study focused on women’s participation in local governance and in decision making structures such as Council, Ward Development Committees (WADCOs), Ward Assemblies, Village Development Committees (VIDCOs), Village Assemblies and Water Point Committees (WPCs). The Liberal Feminist theory was used to guide this study. The liberal feminist movement focuses on eliminating female subordination rooted in customary and legal constraints which blocks women's entrance to and success in the public world (Tong, 1989). This theory applies to this study as there is need to eliminate women’s subordination and to enhance women’s participation in local governance or public space so that their interests and needs are represented and addressed as those of males.